TARUNG STRATEGI KANDIDAT PADA PEMILIHAN BUPATI KABUPATEN TAPANULI SELATAN TAHUN 2020 DI KECAMATAN SIPIROK - Al-Purqon, Satria; ', Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Strategies are defined as any actions that might be taken in organization to set goal or objectives that have been settled. This research talked about the strategies of battle at 2020 in South tapanuli district regent election in sipirok subdistrict. This research aimed to describe strategies of battle between two candidates pair Muhammad Yusuf Siregar - Roby Agusman Harahap and Dolly Putra Parlindungan Pasaribu - Rasyid Assaf Dongoran in district regent election at 2020 in Sipirok subdistrict. The theory used in this research is Peter Schroder's Offensive and Defensive Politics in order to win by utilizing Pierre Bourdieu's modality. This research used qualitative method and by interviewing, documentation and literature review to collect the data. The resources related to the candidates' strategies in the election of district regent by using the quantitative descriptive approach. The research has shown that in the candidates' strategies of battles in the district regent election in South Tapanuli at 2020 require politic strategies to maximize the modality that they have. The modality in candidates' strategies are consist of social capital, economy capital, culture capital, politic capital. Candidate pair that have well strategies and capable to maximize the modality will be the winner in the political election that is carried out. Keywords : Strategy, Modality, Regent Election.